Performance evaluation of lateral canopy shakers with catch frame for continuous harvesting of oranges for juice industry - Sola-Guirado, Rafael R.; Castro-Garcia, Sergio; Blanco-Roldán, Gregorio L.; Gil-Ribes, Jesús A.; González-Sánchez, Emilio J. (International Journal of Agricultural and Biological Engineering, 2020)
Citrus is mainly oriented to fresh consumption, and harvesting is usually performed manually. However, the high cost of harvesting and the low availability of labour can compromise the profitability of the crop when it is destined to juice industry. The development of citrus mechanical harvesting for industrial processing is conditioned to reach a high fruit removal efficiency, with a reduced damage to both fruit and trees. The current machines available are very large, requiring extensive plantations with long rows of trees to be efficient. In this study, two lateral canopy shakers equipped with a catch frame were evaluated to harvest independently both sides of the hedge on intensive citrus plantations with the main objective of determining their performance and feasibility. The lateral canopy shakers tested were three tractor-drawn machines, one commercial machine and two prototypes. The tested machines reached a mean value of 78% of fruit removal. Besides, the prototypes, equipped with a catch frame, were able to recover a mean value of 70% of yield. Although the results were promising, for achieving an efficient result, the application of this harvesting technology still requires a process of improvement, and the adaptation of both the machine and the plantation. The machines should reduce the amount of post-harvest ground fruit (5.9%-10.4%). Tree damages generated by the contact of the catch frame with the trunk and the metal rods with main branches were the most relevant. Therefore, it is still necessary to increase the ground speed of the machinery and improving the design of the rods, regulating the rod penetrating deep in the canopy to improve the fruit recovery and limit the damage caused to the trees.Keywords: harvester, mechanical harvesting, fruit removal, tree damage, Citrus sinensis L. OsbeckDOI: 10.25165/j.ijabe.20201303.4998Citation: Sola-Guirado R R, Castro-Garcia S, Blanco-Roldán G L, Gil-Ribes J A, González-Sánchez E J. Performance evaluation of lateral canopy shakers with catch frame for continuous harvesting of oranges for juice industry. Int J Agric & Biol Eng, 2020; 13(3): 88–93.